Structure and UV-induced photochemistry of 2-furaldehyde dimethylhydrazone isolated in rare gas matrices - Araujo Andrade, C. (2012)
In this work, a combined matrix isolation FTIR and theoretical DFT(B3LYP)/6-311++G(d,p) study of 2-furaldehyde dimethylhydrazone (2FDH) was performed. According to calculations, two E and two Z conformers exist, the E forms having considerably lower energy than the Z forms. The absence of relevant sterical hindrance between the two substituents around the CN bond (dimethylamino and 2-furyl) in the E structures and an extended π-p electron delocalization in the hydrazone moiety determines the higher stability of these species relatively to the Z structures. In the lowest energy form (E-AG) the O-C-CN and CN-N-Lp (Lp = lone electron pair of amine nitrogen atom) dihedral angles are predicted by the calculations to be -177.2° and 93.7°, respectively. The weak (NC)-H⋯O hydrogen bond type interaction (H⋯O distance: 252.2 pm) in form E-AG, together with the absence in this form of the destabilizing interaction between the lone electron pairs of the oxygen and nitrogen atoms existing in E-SG, explains its lower energy in comparison with this latter form. Both E-AG and E-SG conformers could be trapped from room temperature gas phase in low temperature argon and xenon matrices. The high E-SG → E-AG energy barrier (>25 kJ mol-1) explains that, upon increasing the temperature of the matrices no conformational isomerization could be observed. After irradiation of 2FDH with UV-light at λ > 328 and λ > 234 nm, two different photochemistries were observed. Irradiation at lower energy (λ > 328 nm) induced the E-AG → E-SG isomerization. Further irradiation at higher energy (λ > 234 nm) led to a quick consumption of 2FDH and production of furan and dimethylisocyanide.